Penggunaan No Da dalam Kalimat Bahasa Jepang: Kajian Sintaksis dan Semantik - Balqis, Adinda Nabila; Iriantini, Sri (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 2 (2023)DO - 10.24843/JS.2023.v05.i02.p7, 2023)
This research aim to determine the function and meaning of modality no da in Japanese sentences found in various media such as anime. This research was conducted using descriptive qualitative method by collecting data to analyze in the form of sample sentences containing no da modality based on theory according to Noda (1997). The results of this research show that no da is used when the speaker and the interlocutor know the situation set in the conversation. Modality no da has various functions, including : as a nominalizer, expression delivery, question and conjunction that combines one clause with another. The meaning of modality no da varies depending on the function and verb attached to modality no da.